Chronobiological approach in cancer therapy (Experimental biology, 2015)
We propose a method for assessing the general condition of the internal organ systems including desinhronoze disorders of the body on the basis of electro conductivity and temperature indicators ofbiologically active points, which allows the timing of therapeutic intervention in the diurnal rhythm in order to improve the effectiveness of treatment and reduce the side effects of anti-cancer agents. The most optimaltime for therapeutic influence is the period minimal disbalance of electro conductivity and maximal disbalance – temperature of bioactive points and maximal average body temperature.
Keywords: biologycal rhythm; chronobiological approach to treatment